(Relative) autonomism, policy currents and the politics of mobilisation for food sovereignty in the United States: the case of Occupy the Farm*. Issue 6 (3rd June 2018) - Roman-Alcalá, Antonio
ABSTRACT: Food sovereignty movements (FSMs) globally have sought to rearrange relations between land, power, state actions and societal forces outside the state, towards a new ideal of democratised, egalitarian and ecological food systems. The question of how best to reach this ideal has vexed movements and scholars alike, with many anti-capitalist theorists proposing that because of the historical dedication of states to maintaining unequal and unsustainable capitalist relations, change must be pursued outside and against the state rather than through it (i.e. through "autonomism"). Yet, analysis of FSMs globally shows that autonomism is relative, partial and best seen as an aspirational ideal rather than a fixed dogma. This paper deepens this insight by analysing a case within the United States where a local direct action group promoted food sovereignty by illegally occupying public land. The case shows how even apparently autonomist movements can through influence on state and societal actors contribute to state-based "policy currents" that flow in the direction of food sovereignty. This mutual codetermination by actors in and out of state institutions of the possibility and shape of "policy currents" renders state–society relations as important, even to those interested in (relative) autonomism. This paper thus leaves behind dichotomous interpretations of (and recommendations for ) FSMs vis-à-vis autonomism, in order to unpack the influence (in thought) and impact (in action) of autonomist tendencies in food sovereignty construction.